Effects of Valproate and Fluoxetine Combination on YMRS and MADRS Sores in Continuation Phase Treatment of Bipolar Disorder - Trengginas, Ganesha T; Hasmono, Didik; Subagyo, Roni (Folia Medica Indonesiana, 2018)
Valproate is the most common drug to use in bipolar disorder in Indonesia and the only mood stabilizer drug in national formulary. Combination of valproate and fluoxetine are the most used combination in bipolar disorder therapy in Bhayangkara Hospital, Kediri. However, this combination has been controversial because of its risk of triggering mania or hipomania episode in 12 months. The aim of this study was to analyze mood change symptoms with YMRS and MADRS scale after treatment of valproate and fluoxetine combination in continuation phase treatment of bipolar disorder. This cross-sectional, observational study was conducted in psyciatry clinic in Bhayangkara Hospital Kediri between August 2016-October 2016 on 15 patients in YMRS. MADRS questionnaire was filled by physician before treatment and after 8 weeks treatments. Within 8 weeks, mean YMRS score changed from 1.4 to 1.26 (p>0.05). Whereas, mean MADRS score changed from 31.8 to 10.93 (p<0.05) after 8 weeks. There was no significant different in YMRS score between pre- and post-treatment, but there was significant different in MADRS score after treatment.